2002
DOI: 10.1111/j.1574-6941.2002.tb00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of earthworms with indigenous and bioaugmented PCB-degrading bacteria

Abstract: Partial bioremediation of polychlorinated biphenyl (PCB)-contaminated soils has been achieved using bioaugmentation with PCB-degrading bacteria and earthworms. To further study the contribution of earthworms to bioremediation, an experiment was conducted in which the changes in indigenous and bioaugmented PCB-degrading bacteria were analyzed during treatment of contaminated soil using earthworms (Pheretima hawayana) alone or in combination with the PCB-degrading bacteria, Ralstonia eutrophus and Rhodococcus sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…The consumption of humic acid and humin by earthworms in this study therefore releases atrazine from soil aggregates and consequently accelerates its biodegradation. Our findings are consistent with Luepromchai's work that the enhanced removal of polychlorinated biphenyl (PCB) in vermicomposting is attributed to the increasing PCB availability and the abundance of PCB-degraders (Luepromchai et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…The consumption of humic acid and humin by earthworms in this study therefore releases atrazine from soil aggregates and consequently accelerates its biodegradation. Our findings are consistent with Luepromchai's work that the enhanced removal of polychlorinated biphenyl (PCB) in vermicomposting is attributed to the increasing PCB availability and the abundance of PCB-degraders (Luepromchai et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…One possibility is that 1.5 V indirectly stimulates the PCB degradation of microaerophilic or aerobic microorganisms by promoting the movement of aquatic worms, which would actively mix O 2 into the sediment. Such worms have been reported to respond to electric stimuli (Satchell, J.E., 1955) and to stimulate indigenous or bioaugmented biphenyl-degrading bacteria and improve PCB bioremediation (Luepromchai, E. et al, 2002; Singer, A.C. et al, 2001). We observed that worms moved more actively to the surface of sediment in SBRs with the added voltage ( e.g .…”
Section: Resultsmentioning
confidence: 99%
“…The eluted DNA products were stored at Ϫ20ЊC prior to analysis. DNA from each soil sample was subjected to polymerase chain reaction and DGGE as previously described [24].…”
Section: Microbial Community Anlaysismentioning
confidence: 99%